Integrated Hydrological and Hydraulic Modeling for Dam Breach Analysis: A Case Study of Mahadev Khola, Bhaktapur - Manandhar, Roshan; Bhattarai, Santosh; Thakurati, Roma; Maharjan, Surendra; Shrestha, Sujan (Journal of Engineering and Sciences, 2024)
Located in the Mahadev Khola region of Bhaktapur, Nepal, this study explores the essential functions of dams in water storage, hydropower, flood control, and resource management while emphasizing their vulnerability to catastrophic failures despite comprehensive engineering efforts. Historical failures, including those caused by overtopping, excessive inflow, and typhoon-induced breaches, highlight the necessity for robust safety measures. This research uses HEC-HMS for Probable Maximum Flood (PMF) modeling and HEC-RAS for simulating dam breaches for overtopping failure to generate precise outflow hydrographs and flood hazard maps. The model was calibrated using data from the highest observed flood on July 23, 2002, and validated with runoff data from July 9, 1998, achieving strong performance metrics: NSE of 0.86, R² of 0.85, and PBIAS of -6.12% for calibration, and NSE of 0.89, R² of 0.87, and PBIAS of -14.41% for validation. Our findings underscore the importance of detailed hydrological simulations, ongoing monitoring, and reinforcement to mitigate risks. Identifying significant risk zones, the study emphasizes the need for timely evacuations and safety protocols. Ultimately, this research demonstrates the effectiveness of HEC-RAS in enhancing dam safety assessments and improving community resilience against environmental uncertainties and evolving hydrological conditions.